Monitoring And Controlling System Based on Internet of Things (IoT) for Ornamental Chrysanthemum Plants - Roihan Noval; Indri Yanti; Muh Pauzan (International Journal of Engineering Continuity, 2024)
Monitoring and controlling system based on Internet of Things has been developed for ornamental chrysanthemum plants. User interface of the system is a website application created using PHP programming language and MySQL as Database Management Systems. The IoT system built are the result of literature review of chrysanthemum plants, such as an ideal soil moisture for chrysanthemum plants is in the range of 40% to 60%, the average plant water requirement is 16.05 ml/day, it is also recommended to apply liquid fertilizer with a high N content of 2g per litre of water every week. This knowledge then applied in the IoT system. Research findings indicated that the device could be controlled through the website and was capable of transmitting real-time soil moisture data. This system not only triggers watering when the soil humidity falls below 41%RH and stops it when reaching 60%RH but also incorporates scheduled fertilizer according to predetermined schedules, meeting the anticipated outcomes. Water and fertilizer pumps produced volumetric flow rate that changed as the level of liquid in the storage tank decreases. The lower the height, the smaller the volumetric flow rate produced, this is due to the influence of hydrostatic pressure.